Self-Serving Dictators and Economic Growth - Daniel Haile; Abdolkarim Sadrieh; Harrie A. A Verbon (Center for Economic Studies and ifo Institute (CESifo), 2003)
A new line of theoretical and empirical literature emphasizes the pivotal role of fair institutions for growth. We present a model, a laboratory experiment, and a simple cross-country regression supporting this view. We model an economy with an unequal distribution of property rights, in which individuals can free-ride or cooperate. Experimentally we observe a dramatic drop in cooperation (and growth), when inequality is increased by a selfserving dictator. No such effect is observed when the inequality is increased by a fair procedure. Our regression analysis provides basic macroeconomic support for the adverse growth effect of the interaction between the degree and the genesis of inequality. We conclude that economies giving equal opportunities to all are not likely to suffer retarded growth due to inequality in the way economies with self-serving dictators will.
Keywords: 330; inequality; corruption; weak institutions; growth; intentions; dynamic public goods